1995
DOI: 10.1161/01.atv.15.11.1938
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Serum Cholesterol Levels Alters Lesional Composition of Atherosclerotic Plaques

Abstract: We examined whether serum cholesterol reduction alters the lesional composition of atherosclerotic plaques. To reduce serum cholesterol levels, we gave pravastatin sodium, a 3-hydroxy-3-methylglutaryl Coenzyme A reductase inhibitor, to mature Watanabe heritable hyperlipidemic rabbits, an LDL receptor-deficient animal model, for 48 weeks. Atherosclerotic lesions were immunohistochemically and conventionally stained and each lesional component area was measured by a color image analyzer. Compared with those of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
46
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(51 citation statements)
references
References 28 publications
3
46
0
2
Order By: Relevance
“…As in previous studies, we documented that lipid lowering decreased numbers of macrophages in experimental atheroma. 19,20 However, functional attributes of these and other lesional cells have not been investigated heretofore. The results presented here provide an experimental basis for understanding potential mechanisms for stabilization of atheromatous plaques.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As in previous studies, we documented that lipid lowering decreased numbers of macrophages in experimental atheroma. 19,20 However, functional attributes of these and other lesional cells have not been investigated heretofore. The results presented here provide an experimental basis for understanding potential mechanisms for stabilization of atheromatous plaques.…”
Section: Discussionmentioning
confidence: 99%
“…However, the precise molecular and cellular mechanisms that might produce such "stabilization" of atheroma remain conjectural. The classic works of Armstrong et al 16,17 and Small et al, 18 as well as more recent investigations, 19,20 have suggested decreased macrophage number, decreased lipid content, and relative increase connective tissue during lipid lowering in animals. However, these previous studies have not generally addressed the biochemical and molecular aspects of the functions of lesional cells during lipid lowering.…”
mentioning
confidence: 94%
“…For example, HMG-CoA reductase inhibitors such as pravastatin have been shown to inhibit chemotactic migration of monocytes (17) and neutrophils (18) in vitro. Treatment with pravastatin has been shown to reduce the number of monocytes infiltrated into atherosclerotic plaques (19,20) and to reduce metalloproteinase activity (21,22). Furthermore, pravastatin therapy appears to result in reductions in C-reactive protein levels and coronary events after acute myocardial infarctions in patients (23,24).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, simvastatin, a statin, did not decrease serum cholesterol levels in LDLR-KO mice and CETP(+/-)LDLR(-/-)mice, and increased serum cholesterol levels in apoE-KO mice at a dose of 30 mg/kg/day (Yin, 2012), although an extremely high dose of statins (0.168% in diet, 200-300 mg/kg/day) decreased serum cholesterol levels in LDLR-KO mice (Krause, 1998). In contrast, WHHL rabbits, an animal model of familial hypercholesterolemia, have played important roles in studies of the hypocholesterolemic effects and anti-atherosclerotic effects of statins (Shiomi, 1995;). The cholesterol-lowering effect of statins is mainly mediated by an increase in LDLR in liver.…”
Section: Ldlr-deficiency Mild Increase In Plasma Cholesterolmentioning
confidence: 99%
“…Before the development of genetically modified animals, the Watanabe heritable hyperlipidemic (WHHL) rabbit, the first animal model for familial hypercholesterolemia, developed by Yoshio Watanabe in 1980 (Watanabe, 1980), helped to verify a low-density lipoprotein (LDL) receptor-pathway in vivo and to clarify lipoprotein metabolism in humans (Goldstein, 1983), in addition to the process by which atherosclerosis develops (Shiomi, 2009). Furthermore, WHHL rabbits have contributed to the development of hypocholesterolemic agents, statins, (Watanabe, 1981;Tsujita, 1986) and to clarifying anti-atherosclerotic effects (Watanabe, 1988;Shiomi, 1995;. In the present, WHHL rabbits were improved by selective breeding to produce the WHHLMI strain, which suffers from severe and vulnerable coronary atheromatous plaques and myocardial infarction due to coronary occlusion with progression of atherosclerotic plaques (Shiomi, 2003).…”
Section: Introductionmentioning
confidence: 99%